DEVELOPING THE ENTREPRENEURIAL SOUL OF SALAFI STUDENTS AT USHULUDDIN ISLAMIC BOARDING SCHOOL - Nafisatul Laila; Dahlia; M. Abu Nadlir; Ahmad Mustofa (Khidmatan, 2023)
Ushuluddin Bawang Islamic Boarding School is one of the Islamic boarding schools that is required to produce quality students in their fields. Santri must be able to become good entrepreneurs when they are already involved in society. The problem faced by some students is that students are often confused when they finish boarding school what work they should do. There are many reasons behind this, among others, in Islamic boarding schools in general, it prioritizes aspects related to religion, such as how to teach morals and. its application and deepen the study of fiqh and so on, without providing additional insight when it is already in the community. This article is based on his dedication to the Ushuluddin Bawang Islamic boarding school for 21 days. The purpose of this article is to demonstrate the development of an entrepreneurial spirit using the ABCD method. This article was prepared using a descriptive qualitative method. The data was obtained through interviews with students, especially female students and then analyzed with inductive thinking. Based on the results of the analysis using the Asset Based development method, the program being implemented is mentoring to broaden entrepreneurial insights and the mentoring process. This will allow students to feel the positive benefits of the program implemented.